Multiparametric Sensor to Measure Water Quality Parameters Using Internet of Things - Cruz-Mata, Cindy-Noely; Martinez-Montejano, Roberto-Carlos; Robles-Martínez, Marissa; González-Badillo, Germánico; Jaime-Rodríguez, José-Jimmy (Revista Facultad de Ingeniería, 2024)
This study introduces an innovative water quality monitoring system capable of simultaneously measuring six essential parameters (total dissolved solids, oxidation-reduction potential, dissolved oxygen, temperature, pH, and electrical conductivity) by incorporating the Internet of Things technology. Therefore, it is an advanced tool for water resource management. Unlike conventional multiparameter sensors, which are often limited in their storage capacity and number of parameters, our device automatically stores data in Firebase, thus ensuring secure, accessible, and scalable real-time information management. Additionally, in situations of connectivity loss, the system includes an SD card to store data in an Excel file and ensure continuous logging without interruptions. This design not only eliminates the need for sample transportation and handling but also enables precise monitoring from any location. By measuring six distinct parameters, the system provides a comprehensive and customizable view of water quality, adapts to various needs and environments like industry, agriculture, or natural resource conservation. This versatility and technological robustness, supported by Firebase, make our system a key solution for efficient and real-time water monitoring.